A Study of Nonlinear Fractional-Order Boundary Value Problem with Nonlocal Erdélyi-Kober and Generalized Riemann-Liouville Type Integral Boundary Conditions. Issue 2 (4th March 2017) - Ahmad, Bashir; Ntouyas, Sotiris K.; Tariboon, Jessada; Alsaedi, Ahmed
Abstract: We investigate a new kind of nonlocal boundary value problems of nonlinear Caputo fractional differential equations supplemented with integral boundary conditions involving Erdélyi-Kober and generalized Riemann-Liouville fractional integrals. Existence and uniqueness results for the given problem are obtained by means of standard fixed point theorems. Examples illustrating the main results are also discussed.